Rancang Bangun Sistem Pencarian Koleksi Laporan Skripsi Dan PKL dengan Teknologi Web Semantik (Studi Kasus: Ruang Baca Fakultas Ilmu Komputer Universitas Brawijaya) - Prasetyo Iman Nugroho; Bayu Priyambadha; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Library in Faculty of Computer Science (FILKOM) Universitas Brawijaya has many collections which may consists of thesis documents or internship reports with various titles and subjects. Currently there is a search system used to search collections which housed in the library. The system will receive keywords from user and then will perform a search based on the keyword and display the search results. However, the obtained search results may not be relevant from the keyword and not in accordance with user's perceptions and expectations. From this problem there is a solution which is to develop knowledge from library collections with semantic which will be accessed with a web-based system. The ontology is build on collection data using ProtÃ©gÃ© and the system developed using PHP. Result from white box test method using unit test showed that the system has low logic complexity. Meanwhile with black box test method on validation test, the results from all test cases are valid.